Mendelian inheritance of microsatellite markers in Southeast Asian River Catfish, Mystus nemurus - Hoh, Boon Peng; Siraj, Siti Shapor; Tan, Soon Guan; Yusoff, Khatijah (Universiti Putra Malaysia Press, 2005)
Eight previously designed polymorphic microsatellite loci, namely, Mnc434a, Mnc65b, Mnc441, MnBp5-1-02b, MnBp5-1-30b, MnBp5-2-02b, MnBp8-4-43a, and MnBp8-4-43b, were used to examine their modes ofsegregation in Mystus nemurus family study. Randomly selected broodstocks from Terengganu population were used to generate F 1 population. DNA was isolated from tissue samples of the parents, whilst the whole one-month-old F , 1 progeny was used to isolate the DNA. Chi-square analysis was performed to test the significance of the results obtained. It was shown that all the eight microsatellite loci examined segregated close to Mendelian inheritance ratios, which would be useful in generating a genetic linkage map for this species.